Method for preparing 2-amino-4-chlorodiphenyl oxide - GU GAOWEI; REN WENFEI; ZHAO GUOSHENG; WU WEIGUO (2016)
The invention discloses a method for preparing 2-amino-4-chlorodiphenyl oxide. The method comprises the following steps: dispersing 2-amino-4-chlorodiphenyl oxide, ferric chloride hexahydrate and active carbon in ethanol, then adding alkali for adjusting the pH value to 7-9, under heating condition, dropping hydrazine hydrate for performing a reduction reaction, after the reaction is complete, and processing the material to obtain 2-amino-4-chlorodiphenyl oxide. The preparation method has the advantages of mild reaction condition, easy control, and simple reaction equipment, a catalyst and a solvent are repeatedly used, and the 2-amino-4-chlorodiphenyl oxide is friendly to environment, has the advantages of stable product quality, good purity, and high yield, and is in favor of realizing large-scale production. 本发明公开了种2-氨基-4-氯二苯醚的制备方法，包括以下步骤：将2-硝基-4-氯二苯醚、六水氯化铁和活性炭分散于乙醇中，然后加碱调节pH至7～9，在加热条件下滴加水合肼进行还原反应，反应结束后，经过后处理得到所述的2-氨基-4-氯二苯醚。该制备方法反应条件温和、易控，反应设备简单，所用催化剂及溶剂可多次回收利用，对环境友好，产品质量稳定，纯度好，收率高，有利于实现规模化生产。